Fish assemblages, growth pattern and environmental factors in Upper Baleh River, Kapit, Sarawak - Nyanti, Lee; Nur Ezaimah, Binti Idris; Hafida, Binti Bolhen; Jongkar, Anak Grinang; Ling, Teck Yee; Sim, Siong Fong; Soo, Chen Lin; Tonny, Anak Ganyai; Lee, Karen Suan Ping (UNIMAS Publisher, 2019)
A survey of the freshwater fish composition in the upper Baleh River, Sarawak was conducted in 2015. A total of 1,538 specimens, comprising 45 species from ten families were collected using electrofishing devices and cast nets. The family Cyprinidae was the most dominant (62.9%) as well as diverse (42.2%) family, followed by the Gastromyzontidae (30.4%; 22.2%) in the river. The three most dominant species were Tor tambra (18.1%), Lobocheilos ovalis (12.9%), and Parhomaloptera microstoma (11.3%). Shannon’s diversity index, Margalef’s richness index, and Pielou’s evenness index were 2.9, 6.0, and 0.8, respectively, an indication of moderate species diversity. Canonical Correspondence Analysis demonstrate that elevation, stream order and sedimentation were the most significant factors related to fish assemblages in the river, particularly for members of the families Cyprinidae and Gastromyzontidae. The coefficient ‘n’ value in length-weight relationship for Tor tambra, Lobocheilos ovalis, and Parhomaloptera microstoma were determined as 2.92, 2.72, and 3.15, respectively. Tor tambra and Lobocheilos ovalis exhibited a negative allometric growth pattern which could be due to food competition whereas Parhomaloptera microstoma exhibited a positive allometric growth pattern as mountainous forest stream habitat offers favourable environmental conditions. The Fulton’s condition factor of each species indicates that Tor tambra and Lobocheilos ovalis were in poor condition, whereas Parhomaloptera microstoma was in extremely poor condition. It is hypothesized that environmental degradation caused by logging activities have affected the health of the most dominant fish species in the upper Baleh River. Further study should be conducted to determine the underlying factors that are affecting the fish diversity.